2012
DOI: 10.1097/fbp.0b013e3283565248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT5A antagonists in animal models of schizophrenia, anxiety and depression

Abstract: The few available data on the pharmacological effect of 5-HT5A receptors suggest that antagonists may have anxiolytic, antidepressant and antipsychotic activity. The aim of our study was to verify these suggestions in relevant animal models. Two 5-HT5A antagonist ligands, SB-699551-A (N-[2-(dimethylamino)ethyl]-N-[[4'-[[(2-phenylethyl)amino]methyl][1,1'-biphenyl]-4-yl]methyl]cyclopentanepropanamide dihydrochloride) (3-60 mg/kg, intraperitoneally) and A-843277 (N-(2,6-dimethoxybenzyl)-N'[4-(4-fluorophenyl)thiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…128 In addition, 5-HT 5A is expressed in the brain areas such as the cerebral cortex, hippocampus, amygdala and hypothalamus, 129 suggesting that it is potentially involved in stress reactivity and resilience. Indeed, a study demonstrated that 5-HT 5A antagonists could have different sedative, anxiolytic, and anti-depressant properties 130 (Figure 6). These data suggest that valerian, as a 5-HT 5A partial agonist, may act differently depending on what circumstances the subjects were placed and this could possibly explain the inconsistent outcomes among the trials.…”
Section: Discussionmentioning
confidence: 99%
“…128 In addition, 5-HT 5A is expressed in the brain areas such as the cerebral cortex, hippocampus, amygdala and hypothalamus, 129 suggesting that it is potentially involved in stress reactivity and resilience. Indeed, a study demonstrated that 5-HT 5A antagonists could have different sedative, anxiolytic, and anti-depressant properties 130 (Figure 6). These data suggest that valerian, as a 5-HT 5A partial agonist, may act differently depending on what circumstances the subjects were placed and this could possibly explain the inconsistent outcomes among the trials.…”
Section: Discussionmentioning
confidence: 99%
“…MDL 100907 (Tocris Bioscience, Bristol, UK) was dissolved in a minimal amount of 0.1 N HCl and diluted to the appropriate concentration with sterile water, and SB 699551 (Tocris) was dissolved in sterile water. Their doses were chosen based on previous reports by Marona-Lewicka et al (2005) and Winter et al (2004) for MDL 100907 and by Kassai et al (2012) for SB 699551. ASP 5736 (synthesised at the Department of Medicinal Chemistry) was dissolved in sterile water, and its doses were based on work by Yamazaki et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…propanamide dihydrochloride) is the 5-HT 5A receptor antagonist (apparent pK B of 8.0 in 5-CT-induced stimulation of ( 35 S)GTP-gamma-S binding to human 5-HT 5A /HEK 293 cell membranes assay) with a high 5-HT 5A receptor affinity (pK i of 8.5) and at least 30-fold selectivity (except serotonin transporter) for the human 5-HT 5A receptor versus a number of other 5-HT and other CNS receptors (Corbett et al, 2005;Thomas, 2006). The biological activity of SB 699551 has been demonstrated in several in vivo studies (Gonzalez et al, 2013;Kassai et al, 2012), as well as studies from our laboratory (Nikiforuk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, SB-699551-A had no effect in the forced swim test, but induced sedation in rats (87), and, whereas increased cAMP has been linked to positive effects on memory consolidation (88), an impairment of this trait was reported by other investigators, in mice treated with the same 5HT5A antagonist (89). Furthermore, 5HT5A has been identified as an inhibitory autoreceptor that regulates the release of serotonin, if only in the absence of concurrent signaling through 5HT1A receptors (90).…”
Section: Discussionmentioning
confidence: 99%